Comparative advantage patterns and domestic determinants in emerging countries: An analysis with a focus on technology - Daniela Marconi; Valeria Rolli (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
During the last two decades a number of emerging economies have become deeply engaged in technology-intensive production. This has been reflected in their international trade specialization shifting from labour-intensive goods towards capital-intensive ones, and in rapid productivity gains across all manufacturing activities. The paper investigates for a sample of sixteen emerging countries, the linkages between the pattern of revealed comparative advantages (RCAs), captured by a modified version of the Lafay index of international trade specialization, and the competitiveness structure of the domestic manufacturing sector, measured by a set of industry and country-specific variables. Positive and large RCAs are found to be associated with low unit labour costs in both low-technology (high labour-intensive) and medium- or high-tech sectors. On the other hand, domestic accumulation of physical capital is associated with positive and large RCAs in medium- or high technology sectors. The international disadvantage (negative RCAs) in technology-intensive production tends to deepen for countries with low human capital, whereas it diminishes for countries with large domestic markets importing technology through foreign capital goods.
Keywords: F14; O10; 330; revealed comparative advantages; technological up-grading; Komparativer Kostenvorteil; Technologie; Kapitalintensität; Aufstrebende Märkte; Welt